Economic Growth in OIC Countries: The Role of Political Stability - Hikam, Ahmad Nailul; Wau, Taosige; Wibowo, Muhammad Ghafur; Muhdir, Ibnu (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2024)
Economic growth is an important indicator to assess the economic condition of a country. Various factors greatly influence economic growth, and one of the important factors is the country's political stability. This study aims to analyze the factors affecting OIC countries' economic growth. These factors are foreign direct investment, trade openness, human capital, tourism, and political stability. This study uses panel data from 28 OIC countries during the 2006-2020-time span. This study estimates the model using the Generalized Method of Moment (GMM) analysis technique. The estimation results show that all independent variables have a significant positive effect on the economic growth of OIC countries except foreign direct investment, which produces a negative effect. The interaction between political stability and other variables also produces a significant effect. The interaction effect can strengthen the influence of human capital and tourism on economic growth. The resulting interaction effect between political stability with FDI and trade openness weakens its influence on economic growth. Thus, the high political stability needed to increase economic growth in OIC countries depends on its interaction with other factors in economic growth